Mergers and acquisitions in the banking sector: an empirical review of the impact of merger announcement on abnormal returns - Kolehmainen, Martti Eerik Juhani (2009)
A Work Project, presented as part of the requirements for the Award of a Masters Degree in Management from the NOVA – School of Business and Economics